Models of sedimentation of the Bazhenov High-carboniferous Formation in the zone of the tuttleim and Bazhenov Formations - O. V. Khotylev; Yu. A. Gatovsky; N. S. Balushkina; Yu. A. Kotochkova; N. I. Korobova; M. M. Fomina; E. V. Karpova; G. A. Kalmykov (Georesursy, 2024)
A different approach to the typing of the section of the Bazhenov Formation is presented – the identification of the reference section of the Bazhenov high-carbon formation (BHCF). Six packs were distinguished according to lithological and paleontological features, and their general characteristics were given. Also, indicators of the formation conditions are described, that allow to reconstruct the history and evolution of the basin, e. g. tuff and bone-bed horizons, alginate-rich layers, radiolarite layers, spicular limestones and limestones with a «con-in-con» texture, intensely pyritized layers, packs with an abundance of bivalves. Two types of sedimentation models are formed and described: island and intra-basin upland. On the basis of new data and identified features of the paleogeography of the Bazhenov Sea, a general model of the formation of BHCF deposits in the development zone of the Bazhenov and Tutleim formations is proposed.